2016
DOI: 10.21548/32-2-1382
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Amino Acid Addition on Aroma Compounds in Papaya Wine Fermented with Williopsis mrakii

Abstract: The impact of amino acid addition on aroma compound formation in papaya wine fermented with yeast Williopsis saturnus var. mrakii NCYC2251 was studied. Time-course papaya juice fermentations were carried out using W. saturnus var. mrakii NCYC2251, with and without the addition of selected amino acids (L-leucine, L-isoleucine, L-valine and L-phenylalanine). Yeast growth and changes in sugars, °Brix, organic acids and pH were similar, regardless of amino acid addition. L-Leucine addition increased the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…This indicated that the lychee juice was not deficient in nitrogen. These results were in agreement with some studies which showed that nitrogen supplementation in the form of amino acids (individually or mixture) did not have any effect on the rates of fermentation and the concentration of ethanol produced (Garde-Cerdan and AncinAzpilicueta, 2008; Lee et al, 2011Lee et al, , 2013. However, these data must be interpreted with caution and evaluated in relation to the nitrogen status of the juice.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This indicated that the lychee juice was not deficient in nitrogen. These results were in agreement with some studies which showed that nitrogen supplementation in the form of amino acids (individually or mixture) did not have any effect on the rates of fermentation and the concentration of ethanol produced (Garde-Cerdan and AncinAzpilicueta, 2008; Lee et al, 2011Lee et al, , 2013. However, these data must be interpreted with caution and evaluated in relation to the nitrogen status of the juice.…”
Section: Discussionsupporting
confidence: 92%
“…Supplementation with specific amino acids (especially if added singly) may have targeted effects (Trinh et al, 2010;Lee et al, 2011Lee et al, , 2013, relative to the generic effects of adding ammonium or mixed amino acids described above. Therefore, it would be of interest to examine the impact of addition of specific amino acids on the evolution of volatile compounds in lychee wines, which has not been studied in lychee wine fermentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…mrakii NCYC2251 was studied by Lee, Yu, Curran, and Liu (2011). The results revealed that L-Leucine addition increased the production of isoamyl alcohol and some esters such as isoamyl acetate, isoamyl butyrate and isoamyl propionate, while L-isoleucine addition increased the production of active amyl alcohol and active amyl acetate.…”
Section: Papaya (Carica Papaya L)mentioning
confidence: 99%
“…Therefore, the papaya juice fermentation with W. saturnus var. mrakii NCYC2251 in conjunction with the addition of selected amino acid(s) can be an effective way to modulate the aroma of papaya wine (Lee et al, 2011).…”
Section: Papaya (Carica Papaya L)mentioning
confidence: 99%